Perancangan Sistem Kendali Temperatur dan Monitoring Tungku Pembakaran Sampah Berbasis IoT Menggunakan NodeMCU ESP8266 dan Sensor DS18B20 dengan Kontrol PWM Adaptif - Mohammad Yunus; Sumpena Sumpena (Universitas Dirgantara Marsekal Suryadarma, 2026)
Waste management through open burning is still widely practiced by communities; however, the process is often inefficient due to unstable temperature fluctuations and the production of dense black smoke caused by incomplete combustion. This study aims to design an automatic temperature control and remote monitoring system for a waste incineration furnace based on the Internet of Things (IoT) to improve combustion efficiency. The research employed an experimental approach involving hardware design using a NodeMCU ESP8266 microcontroller, a DS18B20 temperature sensor, and an AC Light Dimmer module based on Pulse Width Modulation (PWM) to dynamically regulate fan speed. The system was also integrated with a Telegram-based interface for real-time temperature monitoring. Experimental results over a 75-minute testing period showed that the automatic mode achieved a maximum temperature of 132.45°C, which is higher than the manual mode that only reached 126.94°C. The implementation of PWM control enabled adaptive oxygen supply regulation, increasing the combustion temperature by 5.51°C and accelerating the reduction of black smoke. Therefore, the proposed IoT-based temperature control system successfully improves combustion efficiency while enabling convenient remote monitoring for operational supervision.